Agile and UX Application in Design and Development of Job Portal Web Application - Goh Deng Vee,; Idyawati Hussein,; Mohd Samsu Sajat, (Multidisciplinary Applied Research and Innovation, 2023)
This article describes how User Experience (UX) process is applied in designing and developing a job platform at Universiti Utara Malaysia (UUM). The existing system requires applicants to search through print and visual media for job opportunities. Besides, applicants must apply for the job using forms and other traditional procedures and show for interviews on a specific date and location, which is time-consuming and inconvenient. Employers must post job openings, sort all application information, execute selection procedures, and complete the formalities. This method necessitates a significant amount of time and resources. In this case, recruitment should be timesaving, cost-effective, and, most importantly, identify the best candidate for the job. Job Portal Web Application is a web-based system designed for applicants to find jobs and help the employer find suitable candidates for the job which allows job seekers to identify openings and find qualified candidates for open positions quickly. This web-based system project is carried out using Agile methodology. JPWEBAPP comprises of six functional requirements which are register/login, add, edit, delete, save and display. It is intended to be used by admin and users. Users can register and login to the system with their username and password. The JPWEBAPP can benefit the users, it will be easier to upload and download the files. The web-based system will provide a simple, user-friendly, and manageable platform. It will be easier to upload and download the resume files.